دور القيادة في اكتساب الميزة التنافسية للمؤسسة الاقتصادية - جعفر لعور; نشوة غريسي; مروى فريتح; مريم عثماني (university of eloued جامعة الوادي, 2024)
"كان الهدف من هذه الدراسة التعرف على دور القيادة في تحقيق الميزة التنافسية في مؤسسة "" أومبلاج ميطاليك الجزائرية بولاية البليدة "" , ولتحقيق هدف الدراسة تم الاعتماد على المنهج الوصفي الذي يعتمد على جمع البيانات و ثم تحليلها بواسطة برنامج SPSS, و تمت هذه الدراسة على عينة ضمت جميع العامليين في هذه المؤسسة من اطارات وفنيين و عمال عاديين, وزعت 80 استمارة استبيان على العاملين بالمؤسسة , وتم استرجاع 72 استمارة, منها 65 استمارة استبيان كانت صالحة للتحليل. حيث توصلت الدراسة الى عدة نتائج كان أهمها : وجود دور للقيادة في تحقيق المؤسسة الاقتصادية اذ تهدف المؤسسات الاقتصادية إلى تطوير مهاراتها القيادية التي تساعدها على تحقيق الميزة التنافسية , و قدمت الدراسة عدة توصيات أهمها : تحقيق التوازن بين القيادة والميزة التنافسية وتحويلهما إلى عملية متكاملة و ايضا يجب على المؤسسات الاقتصادية اتباع منهج استراتيجي واضح وفعال في تفعيل القيادة لتحقيق الميزة القدرة التنافسية، وذلك بتوفير كافة المتطلبات الإدارية والفنية و التكنولوجية والبشرية التي تساهم في تحقيق هذا الهدف ." "The aims of this study was to focus on the role of leadership in the continuation of the company “Omblage Italian Metallic Algerian, Blida”. In fact, the aim of the study was to rely on a descriptive structure that relied on data collection and. then analyzing it using the SPSS program. This study was carried out on Artica, which included the factor All were technicians and ordinary workers of this company. 80 questionnaires were distributed to employees of the company, and 72 questionnaires were collected. of which 65 questionnaires were valid for the analysis. The study resulted in several results, the most important of which was: the existence of a leadership role in achieving the economic enterprise, because economic enterprises aim to develop their leadership skills that help them achieve a competitive advantage, and the study presented several recommendations, the most important of which are: achieving a balance between leadership and competitive advantage and transforming them into an integrated process. Economic institutions must also follow a clear and effective strategic approach to activate leadership in order to achieves a competitive advantage, providing all the administratives, technical, technological means and human requirements that contribute to achieving."
Keywords: القيادة; الميزة التنافسية Leadership; competitive advantage